Development of Mathematics Teaching Modules Based on Joyfull Learning - Ulfa, Nanik; Hidayat, Ahmad (Proceedings Series of Educational Studies, 2024)
This research is motivated by the learning process where educators still apply monotonous methods in teaching, which makes students less motivated to learn. The lack of motivation to learn can affect students' learning outcomes, especially in learning mathematics. The solution offered for the problem is the development of Joyful Learning-based teaching materials to improve students' learning outcomes. The method used in this research is the research and development (R&D) model ADDIE with its steps consisting of 5 stages, namely: a) analysis, b) design, c) development, d) implementation, e) evaluation. The objectives of this research are (1) to understand the process of developing Joyful Learning-based mathematics teaching modules for first-grade students at MINU Jati Rejoyoso Kepanjen, (2) to determine the feasibility of Joyful Learning-based mathematics teaching materials in facilitating first-grade students at MINU Jati Rejoyoso Kepanjen in achieving competence in mathematics, and (3) to assess the effectiveness of Joyful Learning-based mathematics teaching modules for first-grade students at MINU Jati Rejoyoso Kepanjen. The research results show that the Joyful Learning-based teaching module is suitable for use as teaching material, as indicated by the assessments from teaching material experts, subject matter experts, and practitioners, each providing a favorable evaluation. The effectiveness of the teaching module is demonstrated by field trial results, which show an improvement in learning outcomes in the cognitive aspect according to the success criteria determined by the researcher. where the percentage of student learning completeness after using Joyful Learning-based teaching materials is 84.21%.